2023
DOI: 10.3390/ijms24065672
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-13 and IL-4 in Adipose Tissue Fibrosis

Abstract: White adipose tissue (WAT) fibrosis, characterized by an excess of extracellular (ECM) matrix components, is strongly associated with WAT inflammation and dysfunction due to obesity. Interleukin (IL)-13 and IL-4 were recently identified as critical mediators in the pathogenesis of fibrotic diseases. However, their role in WAT fibrosis is still ill-defined. We therefore established an ex vivo WAT organotypic culture system and demonstrated an upregulation of fibrosis-related genes and an increase of α-smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…When activated, immune cells highly express factors that promote fibroblast activation. Even though the specific immune cells and the mediators promoting fibroblast activation vary from one fibrotic disease to another, a common feature is the type 2 immune response, more importantly via the secretion of interleukin 13 and 14 (IL-13 and IL-4) produced by T-helper type 2 (TH2) cells, which in turn leads to M2-polarized macrophages with a subsequent release of profibrotic molecules that promote the activation and accumulation of myofibroblasts [18,19]. Myofibroblasts refer to a cellular phenotype characterized by stellate-shaped cells with high levels of intracellular proteins such as non-muscle myosin, alpha smooth-muscle actin (αSMA), and vimentin and differentiated from diverse sources (pericytes, endothelial cells, fibrocytes, epithelial cells, and resident fibroblasts).…”
Section: Pathogenesis Of Fibrosismentioning
confidence: 99%
“…When activated, immune cells highly express factors that promote fibroblast activation. Even though the specific immune cells and the mediators promoting fibroblast activation vary from one fibrotic disease to another, a common feature is the type 2 immune response, more importantly via the secretion of interleukin 13 and 14 (IL-13 and IL-4) produced by T-helper type 2 (TH2) cells, which in turn leads to M2-polarized macrophages with a subsequent release of profibrotic molecules that promote the activation and accumulation of myofibroblasts [18,19]. Myofibroblasts refer to a cellular phenotype characterized by stellate-shaped cells with high levels of intracellular proteins such as non-muscle myosin, alpha smooth-muscle actin (αSMA), and vimentin and differentiated from diverse sources (pericytes, endothelial cells, fibrocytes, epithelial cells, and resident fibroblasts).…”
Section: Pathogenesis Of Fibrosismentioning
confidence: 99%
“…The authors demonstrated that this effect is dependent on WAT-associated macrophages, since their removal by clodronate liposome treatment decreased the fibrotic deposition in WAT in mice intraperitoneally injected with IL-4. A strong positive correlation between fibrosis markers and IL-13/IL-4 receptors was found, but the data seem to indicate that both IL-13 and IL-4 can play a role in ex vivo WAT systems, though only partly in in vivo models [ 18 ].…”
mentioning
confidence: 99%